تحليل المستخلص الميثانولي لكالس نبات الحلبة Trigonella foenum graesum L. تحت الأجهاد المائي مع الماءالممغنط بتقنية الـ (GC-MS) Gas Chromatography-Mass Spectrometry/ Analysis of the Methanelli extract of the Trigonella foenum graesum L circuit. Under wat (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study aimed to study the effect of water stress using different concentration of (0,3,6,9% PEG+1000G.) to induce some chemical compound of Trigonella foenum graesum L. callus. The induction of callus has been done in vitro on MS media by using combination of 2,4-D (0.5, 1, 1.5 mg/L) and BA (0.5, 1, 1.5 mg/L) to reach the best combination for the best highest callus fresh weight for the next experiment. The results showed that the combination (1mg/L  BA) + (1mg/L2,4-D) was the best combination to produce the highest fresh callus of Trigonella , which was used for induced callus.The solvent of methanol was used to extract the secondary metabolites from the induced callus under the stress condition. GC-MS technique was also used to determine the secondary metabolitein sample of methanol extracts of Trigonella callus, which reveald from that there were many compounds (about 12) for all plant samples.